Neonatology simple and easy. Part 1 - Brucknerová, Ingrid (Univerzita Komenského v Bratislave, 2014)
The author of this textbook to introduce to the reader in some detail the characteristic problems of the newborn, as one of the chapters of Paediatrics, from the perspective of a mother as well as a university teacher. Based on my own experience, I have decided to write a text in a form which is not traditional. While writing this book, I focused both on the content and on the structure and form of the text so as to deliver the sequence of steps in assessing the current status of the newborn as closely as possible. Highlighted are the most important thoughts, recommendations and warnings based on our knowledge and experience. Students of general medicine and physicians can find important notes and advices at the end of each chapter that could be used in their studies and future work. I hope that the contents of the book will help medical students in their preparation for practical training in Paediatrics, for exams and the state exam.